1995
DOI: 10.1002/hed.2880170608
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation outcomes of long‐term survivors treated for head and neck cancer

Abstract: This study indicates that T1 larynx patients report many physical complaints even though several years had elapsed since treatment. Also, laryngectomy patients may need psychosocial guidance for a longer posttreatment period and that health care personnel must involve the partner as much as possible in all communications. Commando procedure patients in particular feel hindered by their disfigurement and its consequences. Future research with respect to validation of the specific head and neck modules is needed. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
89
1
5

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(98 citation statements)
references
References 32 publications
3
89
1
5
Order By: Relevance
“…This exacerbation of psychological symptoms may be due to chronic stress caused by the threatening presence of the disease and the distress caused by trying to maintain a normal and healthy appearance (de Boer et al, 1995). Similarly, a study conducted by De Boer et al (1995) which supports the previous findings, found that over half of the patients who had undergone laryngectomy reported having their appearance highly damaged by such treatment, with the highest levels of complaints being among women. This study also showed that even 2 years after treatment, patients still reported feeling of uncertainty, low self-esteem, depression, anxiety, sexual problems and trouble managing their emotions (de Boer et al, 1995).…”
Section: Cancer Treatment and Side-effectsmentioning
confidence: 65%
See 3 more Smart Citations
“…This exacerbation of psychological symptoms may be due to chronic stress caused by the threatening presence of the disease and the distress caused by trying to maintain a normal and healthy appearance (de Boer et al, 1995). Similarly, a study conducted by De Boer et al (1995) which supports the previous findings, found that over half of the patients who had undergone laryngectomy reported having their appearance highly damaged by such treatment, with the highest levels of complaints being among women. This study also showed that even 2 years after treatment, patients still reported feeling of uncertainty, low self-esteem, depression, anxiety, sexual problems and trouble managing their emotions (de Boer et al, 1995).…”
Section: Cancer Treatment and Side-effectsmentioning
confidence: 65%
“…That is, the levels of depression and anxiety among those patients were seen to increase with time (Rapoport et al, 1993). This exacerbation of psychological symptoms may be due to chronic stress caused by the threatening presence of the disease and the distress caused by trying to maintain a normal and healthy appearance (de Boer et al, 1995). Similarly, a study conducted by De Boer et al (1995) which supports the previous findings, found that over half of the patients who had undergone laryngectomy reported having their appearance highly damaged by such treatment, with the highest levels of complaints being among women.…”
Section: Cancer Treatment and Side-effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results are not only cosmetic, but also functional defects, such as swallowing, chewing, breathing disorders and voice production deterioration. Early detection of these tumours is therefore one of the most important factors of treatment success [2].…”
Section: Introductionmentioning
confidence: 99%